Exploring Interest in Malaysia's History Among PERMATA Insan College Students: A Mini Survey - Aisy Nazeem Mohd Khairul Nizam; Hadief Arfan Khairul Rizal; Nafiz Zafri Noraizuddin; Shafinah Kamarudin; Mahiz Spawi; Siti Munirah Mohd (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan